2012
DOI: 10.1101/cshperspect.a007799
|View full text |Cite
|
Sign up to set email alerts
|

The Hygiene Hypothesis: An Explanation for the Increased Frequency of Insulin-Dependent Diabetes

Abstract: The steadily increasing frequency of insulin-dependent diabetes in several countries is best explained today by the decline of infections. Epidemiologic and animal data support this conclusion, which, however, requires confirmation by intervention trials in man. The mechanisms of the protective effect of infections on diabetes onset are diverse including competition for homeostatic factors and stimulation of regulatory T cells and of Toll-like receptors. These considerations might have interesting therapeutic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
101
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(107 citation statements)
references
References 62 publications
4
101
0
2
Order By: Relevance
“…Collective hygiene is also essential. However, the sanitary quality of drinking water and food (cold chain), vaccination (as mentioned above), or the excessive use of antibiotics that affect gut flora may be more important than individual hygiene (Bach & Chatenoud, 2012). RibouletBisson et al (2012) revealed that Lactobacillus salivarius UCC118 administration had an effect on genus Firmicutes members in pig and mice.…”
Section: The Gut Microbiome and Hygiene Indulgencementioning
confidence: 99%
“…Collective hygiene is also essential. However, the sanitary quality of drinking water and food (cold chain), vaccination (as mentioned above), or the excessive use of antibiotics that affect gut flora may be more important than individual hygiene (Bach & Chatenoud, 2012). RibouletBisson et al (2012) revealed that Lactobacillus salivarius UCC118 administration had an effect on genus Firmicutes members in pig and mice.…”
Section: The Gut Microbiome and Hygiene Indulgencementioning
confidence: 99%
“…Genetic predisposition, environmental influences, vitamin D processing, and viruses have been identified as the most likely agents in pathogenesis of T1DM. 4,5 To this date, however, there is no robust evidence identifying its main causes.…”
Section: Introductionmentioning
confidence: 99%
“…Such geographical variations have also been found in other autoimmune diseases such as multiple sclerosis and inflammatory bowel disease. [5][6][7] The underlying mechanism of the disease has been debated widely. Genetic predisposition, environmental influences, vitamin D processing, and viruses have been identified as the most likely agents in pathogenesis of T1DM.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, if enteroviruses play a major role in T1DM pathogenesis, how could we explain the increase in T1DM incidence in countries where exposure to these microorganisms has been dropping, such as Fin- Role of IFIH1 in the development of type 1 diabetes land? Are the data showing that T1DM can be caused by viral infections compatible with the hygiene hypothesis (17)? Interestingly, data in NOD mice revealed that coxsackieviruses provoke diabetes only when a preexis ting mass of insulitis has accumulated.…”
Section: Introductionmentioning
confidence: 99%